Dilema Administrasi dan Agama: Implementasi SPTJM di Jantung Minangkabau (Studi Kasus Kecamatan Harau) - Susanti, Meria; Silvianetri, Silvianetri; Elimartati, Elimartati; Atsani, Ulya; Nofialdi, Nofialdi; Yunarti, Sri (IDRIS Darulfunun Institute, 2026)
Unregistered marriages (nikah siri) remain a significant social phenomenon in the Minangkabau community, particularly in Harau District, Lima Puluh Kota Regency, West Sumatra. To address administrative barriers for children from these marriages, the government implemented the Absolute Statement of Responsibility (SPTJM) policy based on Minister of Home Affairs Regulation Numbers 108 and 109 of 2019, which allows for the inclusion of